Determinants of the VAT Gap in EU Member States from 2000 to 2016 - Kelm, Robert (Central European Journal of Economic Modelling and Econometrics, 2022)
The spectacular surge of Poland’s VAT revenues after 2015 prompted a discussion about the role of the tax administration in collecting tax liabilities. Unfortunately, the scarcity of the available data prevents empirical studies from reaching reliable conclusions about the determinants of VAT revenues. Given that, this article presents a wider attempt at identifying the determinants of VAT revenues in the EU Member States. Using panel cointegration methods, several working hypotheses linking VAT gap to income factors, the business cycle, tax carousels, and an effectiveness of the government are evaluated. The results of the research provide evidence that the VAT gap in the EU countries is under a strong influence from variables approximating changes in per capita incomes, the business cycle, and the openness of an economy to intra-EU trade. The latter finding is a sufficient indication that the improvements made to Poland’s tax system were both legitimate and effective.